The composition of the stent microbiome is associated with morbidity and adverse events during endoscopic drainage therapy of pancreatic necroses and pseudocysts - Frost, Fabian; Khaimov, Valeria; Senz, Volkmar; Weiss, Stefan; Klußmann-Fricke, Bastian; Rühlemann, Malte; Bang, Corinna; Franke, Andre; Pickartz, Tilman; Budde, Christoph; Aghdassi, Ali A.; Siewert, Stefan; et al. (Frontiers in Medicine, 2024)
Background Development of pancreatic necroses or pseudocysts are typical complications of pancreatitis and may require endoscopic drainage therapy using metal or plastic stents. Microbial infection of these lesions poses a major challenge. So far, the composition and significance of the microbial colonization on drainage stents are largely unknown although it may impact outcomes during endoscopic drainage therapy. Methods A total of 26 stents used for drainage of pancreatic lesions were retrieved and the stent microbiome was determined by 16S rRNA gene sequencing. Additional analysis included comparison of the stent microbiome to the intracavitary necrosis microbiome as well as scanning electron microscopy (SEM) and micro-computed tomography (μCT) imaging of selected metal or plastic stents. Results The stent microbiome comprises a large proportion of opportunistic enteric pathogens such as Enterococcus (14.4%) or Escherichia (6.1%) as well as oral bacteria like Streptococcus (13.1%). Increased levels of opportunistic enteric pathogens were associated with a prolonged hospital stay (r = 0.77, p = 3e−06) and the occurrence of adverse events during drainage therapy (p = 0.011). Higher levels of oral bacteria were associated (r = −0.62, p = 8e-04) with shorter durations of inpatient treatment. SEM and μCT investigations revealed complex biofilm networks on the stent surface. Conclusion The composition of the stent microbiome is associated with prolonged hospital stays and adverse events during endoscopic drainage therapy, highlighting the need for effective infection control to improve patient outcomes. In addition to systemic antibiotic therapy, antimicrobial stent coatings could be a conceivable option to influence the stent microbiome and possibly enhance control of the necrotic microflora.